First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Inland waterway traffic noise prediction model: a comparison - B. L. Dai; N. Sheng; J. Huang; F. H. Mu; X. Chen; T. Li; J. M. Xu; Y. L. He (International Journal of Environmental Science and Technology, 2024)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Clinical characteristics of 154 patients suspected of having Ebola virus disease in the Ebola holding center of Jui Government Hospital in Sierra Leone during the 2014 Ebola outbreak - T. Yan; J. Mu; E. Qin; Y. Wang; L. Liu; D. Wu; H. Jia; Z. Li; T. Guo; X. Wang; Y. Qin; Y. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

A novel microbead-based microfluidic device for rapid bacterial identification and antibiotic susceptibility testing - J. He; X. Mu; Z. Guo; H. Hao; C. Zhang; Z. Zhao; Q. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Apoptosis repressor with caspase recruitment domain is regulated by MAPK/PI3K and confers drug resistance and survival advantage to AML - P. Y. Mak; D. H. Mak; H. Mu; Y. Shi; P. Ruvolo; V. Ruvolo; R. Jacamo; J. K. Burks; W. Wei; X. Huang; S. M. Kornblau; M. Andreeff; et al. (Apoptosis, 2014)

Cloning and expression analysis of follicle-stimulating hormone and luteinizing hormone receptor during the reproductive cycle in Korean rockfish (Sebastes schlegeli) - Wei J. Mu; Hai S. Wen; Feng He; Ji F. Li; Miao Liu; Yuan Q. Zhang; Jian Hu; Bao X. Qi (Fish Physiology and Biochemistry, 2013)

Expression profiles of seven channel catfish antimicrobial peptides in response to Edwardsiella ictaluri infection - J W Pridgeon; X Mu; P H Klesius (Journal of Fish Diseases, 2012)
Using quantitative polymerase chain reaction (QPCR), the relative transcriptional levels of seven channel catfish antimicrobial peptide (AMP) genes (NK‐lysin type 1, NK‐lysin type 2, NK‐lysin type 3, bactericidal permeability‐increasing protein, cathepsin D, hepcidin and liver‐expressed AMP 2) in response to Edwardsiella ictaluri infection were determined. None of the AMP genes tested was significantly upregulated at 2 h post‐infection. Hepcidin was the only one that was significantly ( P P E. ictaluri , all lethal doses were able to induce significant ( P In vitro growth studies revealed that the presence of synthetic hepcidin peptide at a concentration of 16 μ m or higher significantly inhibited the cell proliferation of E. ictaluri . Taken together, our results suggest that hepcidin might play an important role in the channel catfish defence against E. ictaluri infection.

The chromosomal localization, expression pattern and polymorphism analysis of porcine FSCN1 gene differently expressed from LongSAGE library - Zh. L. Tang; X. J. Zhang; Sh. L. Yang; Y. L. Mu; W. T. Cui; H. Ao; K. Li (Molecular Biology Reports, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Plant regeneration from in vitro -cultured seedling leaf protoplasts of Actinidia eriantha Benth - Y.-J. Zhang; Y.-Q. Qian; X.-J. Mu; Q.-G. Cai; Y.-L. Zhou; X.-P. Wei (Plant Cell Reports, 1998)